Journeys to Sugaropolis : the Australian South Sea Islander story of the Gold Coast region - Rains, Kevin; Gold Coast (Qld.). Council ([Surfers Paradise, Queensland] : City of Goldcoast, 2013)
"This book looks at the lives and contributions of Australian South Sea Islanders - those early indentured labourers and their descendents - to the Gold Coast and nearby areas"--Page 5.
Cover title.
Logos at foot of title: Australian South Sea Islanders 150 years ; City of Goldcoast.
Includes bibliographical references (pages 61-62).
Also available online. Address as at 05/02/2014
Keywords: Melanesians -- Queensland -- Gold Coast Region -- History; Australian South Sea Islanders -- Queensland -- Gold Coast Region -- History; Indentured servants -- Queensland -- Gold Coast Region -- History; Sugarcane -- Queensland; Sugar trade -- Queensland -- Gold Coast Region -- History; Sugar workers -- Queensland -- Gold Coast Region -- History; Blackbirding -- Queensland -- Gold Coast Region -- History; Gold Coast Region (Qld.) -- History; Australian